PACTA : Rural Development in Honduras through Access to Land and the Development of Productive Enterprises - Korczowski, Thomas; Reyes, Hiska; Galeana, Fernando; Pichón, Francisco (World Bank, Washington, DC, 2012)
This note centers on the Honduras Access to Land Pilot Project (PACTA). PACTA's objectives are twofold, to: (1) facilitate access to land for landless households through the land market; and (2) promote the development of sustainable rural enterprises. PACTA's achievements, thus far, can be summarized as follows: 1) It established a working model for rural enterprise formation that leverages private sector financing. 2) Grants made to families are used to establish productive projects, leverage a proportionally large private investment, and improve access to land. 3) Twenty-seven group productive enterprises and 54 individual enterprises have been established in 24 municipalities in 10 departments in Honduras, benefiting 414 families. No enterprise is in arrears on loan repayment. 4) The program's methodology has been validated in different regions with very different social and environmental conditions. 5) Institutional alliances have been established on a local level in support of the target population. 6) Participatory monitoring and evaluation has proven to be an essential component in the process and enabled PACTA not only to make a number of adjustments in a timely manner but to generate a stronger foundation for moving beyond the pilot phase.